ERRATUM of JNSPOI 2019 Volume 3 Issue 5 - Aryal, Sameer; Adhikari, Binod; Agrawal, Reshu; Bhuju, Krishna Gopal; Karki, Riswas (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
The online version of the “Periodontal Status of Patients with Non -Insulin Dependent Diabetes Mellitus” available at: http://j.nspoi.com.np/index.php/JNSPOI/article/view/78/62 (Aryal S, Adhikari B, Agrawal R, Bhuju KG, Karki R. Periodontal Status of Patients with Non -Insulin Dependent Diabetes Mellitus. J Nepal Soc Perio Oral Implantol. 2019;3(5):2-5.) has been updated according to the respective authors’ request published in JNSPOI Vol. 5 No. 1 Issue 9. The following lines were found to be missing in the “METHODS” section: “The data collection was done from September 2018 to November 2018.” Dr. Sameer Aryal,1 Dr. Binod Adhikari,1 Dr. Reshu Agrawal,2 Dr. Krishna Gopal Bhuju,1 Dr. Riwas Karki1 1Department of Dentistry, Nepalese Army Institute of Health Sciences, Shree Birendra Hospital (SBH), Kathmandu, Nepal; 2School of Public Health, Patan Academy of Health Sciences, Lalitpur, Nepal